On-court position and handedness in visual anticipation of stroke direction in tennis - Loffing, F.; Sölter, F.; Hagemann, N.; Strauss, B. (Psychology of Sport and Exercise, 2016)
Objectives: In racket sports, players integrate information picked up from their opponent's kinematics and contextual cues like on-court position into shot outcome anticipation. In view of suggested difficulties with anticipating left-handed opponents' action intentions, here we examined whether an opponent's handedness interacts with position-dependency in visual anticipation. Design and method: Following a 2 (Group) x 2 (Handedness) x 2 (Position) x 3 (Temporal Occlusion) factorial design, 20 tennis players and 20 non-players predicted directional outcome of temporally manipulated point-light animations of identical left- and right-handed forehand groundstrokes performed near vs. far from the court's midline. Results: Tennis players' response selection was mostly affected by an opponent's on-court position, particularly at an early stage of a hitting movement. Opponents' handedness affected response selection similarly in both groups (i.e., bias towards down-the-line predictions against left-handed strokes occluded at racket-ball-contact), but it did not interact with on-court position. Conclusions: Findings highlight that on-court position, and opponents' handedness to some extent as well, appears relevant for skilled visual anticipation in tennis.